Investigating the Role of LINE-1 Retrotransposons in Primate Brain Evolution - Domitrović,Lucian (2025)
Transposable elements compose roughly 50% of the human genome and have been proven to have a great impact on the genome as a source of genetic variation. Because of this they are normally silenced by various mechanisms one of which being CpG DNA methylation. In this study We analysed the insertional landscapes and methylation levels of reference LINE-1 elements in humans, chimpanzees and rhesus monkeys using their most complete reference genomes supplemented with non-reference insertions identified from Oxford Nanopore Sequencing data. The aims were to look for indications that the retrotransposition process is regulated differently or influenced by different selection pressures between the species and to identify LINE-1 loci that could play a role in the development of the primate brain and thus could have influenced primate brain evolution. By comparing the number of full-length species-specific intragenic vs. intergenic LINE-1 insertions we identified that their number is approximately equal in humans while in other non-human primate species there is a bias towards intergenic insertions. Furthermore, we analysed the LINE-1 methylation in induced pluripotent stem cells (iPSC) and cerebral organoids used as a model for brain development in this study. Cerebral organoids used in this study have been shown to have a correct morphology and express marker genes involved in neural development. These data have shown that the CpG methylation levels are high along the sequence of full-length species-specific LINE-1s in all species in this study while the methylation is more distributed in the LINE-1 promoter region. From these data we investigated the expression of L1Pt loci with low promoter methylation in chimpanzee cerebral organoids and identified two loci with bidirectional promoters transcribing previously undescribed lncRNAs. These two lncRNAs seem to be expressed in chimp iPSCs and have a peak in fold-change expression at 15 days post differentiation of cerebral organoids. It is intriguing that this occurs at a timepoint when we observed a general genome wide rise in LINE-1 methylation levels. Although the results are still very preliminary, they provide a potential target for the future study of genetic causes for differences in the development of chimpanzee and human brains.